Effect of Low Versus High-Heeled Footwear on Spinopelvic Alignment at Different Phases of Menstrual Cycle in Young Adult Women: A Biopsychosocial Perspective - El-Shafei, Manal A.; Yousef, Amel M.; Hamada, Hamada A.; Mohamed, Mohamed F.; Al-Shenqiti, Abdullah M.; Koura, Ghada M. R.; López Sánchez, Guillermo F. (Frontiers in Psychology, 2021)
High heeled shoes adversely affect spinal curvature, increase risk of low back pain and disturb normal gait pattern. The purpose of this study was to examine, from a bio-psychosocial point of view, the combined effect of wearing two different heel heights and of hormonal oscillation throughout different phases of menstrual cycle on spinopelvic alignment. Seventy females with average age of 20.42±1.51 participated in this study, wearing each female two different heel heights: low (2.5 cm) and high (7 cm). Spinopelvic alignment was evaluated by raster-stereography formetric 3D analysis during early follicular, ovulatory and mid-luteal phases of the menstrual cycle. Statistical analysis showed that there was no significant difference (p>0.05) on spinopelvic alignment (kyphotic angle, trunk inclination and pelvic inclination) between wearing low or high heeled shoes during early follicular, ovulatory and mid luteal phases of menstrual cycle. Considering that high-heeled shoes are traditionally associated with femininity, body image, beauty and charm, this research has important bio-psychosocial implications that should be explored in detail in future studies.